Effect of Apolipoprotein E Polymorphism on Serum Uric Acid Levels in Healthy Subjects. (1st April 2005) - Liberopoulos, Evagelos N.; Miltiadous, George A.; Athyros, Vasilios G.; Ganotakis, Manolis; Cariolou, Marios; Bairaktari, Eleni; Elisaf, Moses S.
Abstract : Background: We have previously shown that apolipoprotein E (apo E-) polymorphism may affect serum creatinine concentration and predicted glomerular filtration rate in healthy individuals. On the other hand, there are limited data regarding the possible influence of apo E- polymorphism on serum uric acid (SUA) levels. Methods: Two hundred ninety (148 male, 142 female) apparently healthy white individuals were studied. apo E- genotypes, serum lipid parameters including apolipoproteins, insulin resistance using the homeostasis model assessment (HOMA) as a marker, serum and urine creatinine levels, and serum and urine uric acid concentration were determined in all participants. Results: The apo E-2 allele was associated with lower serum levels of total cholesterol, higher levels of triglycerides and apo E-, and increased serum creatinine concentration compared with the apo E-3 and apo E-4 alleles in our population. Furthermore, the apo E-2 allele was associated with higher SUA levels (321.3 ± 101.1 μmol/L [5.4 ± 1.7 mg/dL]) compared with the apo E-3 allele (261.8 ± 89.2 μmol/L [4.4 ± 1.5 mg/dL]; p = .012) and the apo E-4 allele (243.9 ± 65.4 μmol/L [4.1 ± 1.1 mg/dL]; p = .010), whereas the apo E-2 allele was associated with a nonsignificant decrease in the fractional renal excretion of uric acid (FEUA) compared with the apo E-3 and apo E-4 alleles (7.9 ± 2.2% vs 8.7 ± 4.2% vs 8.9 ± 5.1%, respectively; p = .53). These observations remained statistically significant when the effect of apo E- polymorphism on SUA levels was adjusted for gender, age, systolic and diastolic blood pressure, body mass index, serum creatinine, and triglyceride and apo E- levels, as well as for HOMA index and FEUA. Conclusions: Our data provide evidence, for the first time, that the apo E-2 allele is independently associated with increased SUA levels in healthy individuals.